31P NMR of the pyruvate kinase reaction: An undergraduate experiment in enzyme kinetics. Issue 6 (30th July 2017) - Werner, R. Marshall; Johnson, Austin
Abstract: Understanding how to perform an enzyme assay is a critical learning skill in the undergraduate biochemistry curriculum. Students in biochemistry typically have been exposed to the use of NMR spectroscopy as a tool to determine chemical structure, but rarely are they exposed to the utility of NMR to evaluate enzyme kinetics. Furthermore, coverage of NMR experiments utilizing "alternative nuclei", such as 15 N, 19 F, and 31 P may be neglected. Herein we report a simple 31 P NMR tube experiment that allows students to examine the enzyme kinetics and equilibrium constant of the reaction catalyzed by pyruvate kinase. © 2017 by The International Union of Biochemistry and Molecular Biology, 45(6):509–514, 2017.